Sharia Compliance in Indonesian Pension Funds: Regulatory Challenges and Institutional Practices - Muhamad Afif Sholahudin; Oyo Sunaryo Mukhlas; Mega Silvia (KEDJATI Journal of Islamic Civilization, 2025)
Sharia-compliant pension funds constitute an important component of Islamic finance and social security development in Indonesia, yet their implementation remains institutionally and regulatorily complex. This study examines the application of Sharia economic law in the management of Employer-Sponsored Pension Funds (DPPK) and Financial Institution Pension Funds (DPLK) within Islamic financial institutions, drawing on case analyses of DPLK Syariah Muamalat and the ongoing Sharia transformation of PT TASPEN. Using a qualitative descriptive design, the study applies normative-juridical analysis, regulatory review, and secondary-data-based case examination. The findings indicate that, despite the presence of a comprehensive regulatory framework including Law No. 11 of 1992, POJK No. 33/POJK.05/2016, and DSN-MUI fatwas, Sharia pension fund implementation faces persistent structural constraints, particularly regulatory fragmentation, limited public literacy, and restricted availability of Sharia-compliant investment instruments. The case analysis shows that DPLK Syariah Muamalat has complied mainly with Sharia principles, although further development is required in digital governance and portfolio diversification. Similarly, PT TASPEN’s transition toward a Sharia-based pension system demonstrates institutional potential but remains contingent on strengthened organizational capacity and adequate Sharia supervision. The study highlights the need for regulatory harmonization, the reinforcement of Sharia Supervisory Boards, and the strategic integration of pension funds with Islamic social finance instruments to enhance institutional sustainability. Hence, this research contributes to the discourse on Islamic finance governance by clarifying how regulatory design and institutional practice shape the viability of Sharia-compliant pension systems in emerging Islamic financial markets.